The town traveller - Gissing, George, 1857-1903 (Floating Press, 2010)
Typically known for his hard-hitting works of social realism, such as the novel New Grub Street, the publication of The Town Traveller represented something of a departure for Victorian-era novelist George Gissing. Not only is the novel markedly different in style and tone from Gissing's previous work, but it outsold all of his other publications by a significant measure and lifted him from semi-obscurity to the upper echelons of literary acclaim. Packed with intrigue and emotional heft, The Town Traveller is an engrossing read for fans of nineteenth-century fiction.